2017
DOI: 10.1038/s41467-017-00137-y
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 microRNA-dependent control of leukotriene signaling regulates the transition of hematopoietic niche in mice

Abstract: Hematopoietic stem and progenitor cells arise from the vascular endothelium of the dorsal aorta and subsequently switch niche to the fetal liver through unknown mechanisms. Here we report that vascular endothelium-specific deletion of mouse Drosha (Drosha cKO), an enzyme essential for microRNA biogenesis, leads to anemia and death. A similar number of hematopoietic stem and progenitor cells emerge from Drosha-deficient and control vascular endothelium, but Drosha cKO-derived hematopoietic stem and progenitor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Unlike the previously identified transcriptional regulators of EHT such as Runx1 or Gfi1 / Gfi1b 28 , the leukotriene pathway will be easier to exploit in a translational setting because of the ready availability of small molecule agonists and antagonists. Leukotrienes are produced in a multi-step process from arachidonic acid, which can be metabolised into a number of distinct functionally active molecules, all with their own receptors and spectrum of biological activities, including the fine-tuning of haematopoietic stem cell activity at the time of their first emergence in the aorta-gonad-mesonephros region at E11.5 29 . Of note, the arachidonic acid derivatives prostaglandin and epoxyeicosatrienoic acid have been identified in small molecule screens for compounds that can amplify blood stem and progenitor cells 30 , 31 , and have already entered clinical trials to enhance blood stem cell transplantation 32 .…”
mentioning
confidence: 99%
“…Unlike the previously identified transcriptional regulators of EHT such as Runx1 or Gfi1 / Gfi1b 28 , the leukotriene pathway will be easier to exploit in a translational setting because of the ready availability of small molecule agonists and antagonists. Leukotrienes are produced in a multi-step process from arachidonic acid, which can be metabolised into a number of distinct functionally active molecules, all with their own receptors and spectrum of biological activities, including the fine-tuning of haematopoietic stem cell activity at the time of their first emergence in the aorta-gonad-mesonephros region at E11.5 29 . Of note, the arachidonic acid derivatives prostaglandin and epoxyeicosatrienoic acid have been identified in small molecule screens for compounds that can amplify blood stem and progenitor cells 30 , 31 , and have already entered clinical trials to enhance blood stem cell transplantation 32 .…”
mentioning
confidence: 99%
“…S4A), demonstrating efficient deletion of Drosha in endothelial cells. Vasculogenesis and angiogenesis appeared superficially normal in Drosha cKO EC embryos; however, all cKO EC embryos died around E14.5 to E15.5 due to a hematopoiesis defect (27). Immunofluorescence staining of the endothelial marker CD31 showed that branching of blood vessels was reduced by 20% in the yolk sacs of cKO EC embryos at E13.5 compared to those of control embryos (fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, inactivation of endothelial cell–specific miR-126 is sufficient to cause ISV defects similar to those observed in Drosha morphants in zebrafish (33). However, miR-126 biogenesis is independent of Drosha (33), and the abundance of miR-126 is not affected in Drosha morphants or Drosha cKO EC mice (27). Thus, future studies are necessary to identify endothelial cell–specific miRNAs that are essential for the vascular development and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate m 6 A levels by directing METTL3 binding to mRNAs in a sequence-dependent and AGO2-independent manner. In addition to miR-223, miR-142 and let-7 are also required for HSC formation [61, 62], and numerous miRNAs are differentially expressed during EHT in mouse [63], suggesting that this class of small RNAs will likely have a central role in modulating EHT gene expression levels, be it through epigenetic, epitranscriptomic or posttranscriptional gene regulation.…”
Section: Discussionmentioning
confidence: 99%